A parametric pilot/control device model for rotorcraft biodynamic feedthrough analysis - Masarati, P.; Bindolino, G.; Quaranta, G. (My University, 2014)
This work presents a numerical model of the pilot/control device subsystem. The model is related to the left arm of a helicopter pilot holding a conventional collective control inceptor. A detailed biomechanical model of the pilot is developed within a general purpose multibody dynamics formulation. Linearized models about reference conditions are computed from the general analysis, for specific reference positions of the control inceptor and settings of the neuro-musculo-skeletal system that characterize specific flight conditions and tasks. The linearized models of the biodynamic feedthrough are used to produce coupled pilot/control device subsystem models that are parametrized with respect to the pilot biodynamic feedthrough characteristics and the mechanical properties of the control inceptor.